In Preparation for Outdoor Pharming: Griffithsin Can Be Expressed in Nicotiana excelsiana and Retains Activity After Storage as Silage - Eapen, Paul; Cates, Jennifer; Mundell, Rich; Palmer, Kenneth E.; Fuqua, Joshua L. (Frontiers in Bioengineering and Biotechnology, 2020)
Griffithsin is an algae-derived lectin with strong anti-viral activity against HIV and a positive safety profile. Multiple clinical studies are investigating griffithsin’s utility as topical HIV microbicide. HIV microbicides are an extremely cost-sensitive market and plant-based griffithsin protein expression has the potential to meet those demands. The griffithsin product used in the clinic has been expressed and purified in N. benthamiana, using a TMV-based viral vector system, Geneware ®. Outdoor pharming of biopharmaceuticals would further alleviate startup costs for biotechnology firms and may allow broader product accessibility. Therefore, this study assessed expression in a hybrid tobacco line, N. excelsiana, that is susceptible to TMV-based viral vectors and can be grown outdoors. In addition to using this hybrid line we expand on methods for in planta storage of griffithsin in leafy plants by ensiling kilogram quantities of griffithsin. The ensiling process allows year-round biomanufacturing, minimal environmental-controlled storage, and reduces the industry need for multiple growth areas to maintain multi-product manufacturing of plant-based pharmaceuticals. This study shows that griffithsin can be expressed in N. excelsiana and is stable, recoverable, and active from ensiled tissue. These studies can pave the way for future plant-based pharmaceuticals to be expressed and stored in this manner.